2012
DOI: 10.1002/imhj.20332
|View full text |Cite
|
Sign up to set email alerts
|

Development of parenting self‐efficacy in mothers of infants with high negative emotionality

Abstract: Maternal parenting self-efficacy (PSE) is a potential target for infant mental health interventions because it is associated with a number of positive outcomes for children and mothers. Understanding the development of maternal PSE under conditions of increased parenting stress, such as parenting an infant who is easily distressed and difficult to soothe, will contribute to providing more effective interventions. This study examines the development of maternal PSE in mothers of infants with high negative emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 43 publications
2
61
0
3
Order By: Relevance
“…Scores from the ten items were summed to indicate parenting-related self-efficacy (Teti and Gelfand, 1991). The scale has good reliability and validity (Teti and Gelfand, 1991) and has been used in many studies with new mothers during the first postpartum year (Jones and Prinz, 2005; Leerkes and Crockenberg, 2002; Reece and Harkless, 1998; Schneewind and Pfeiffer, 1995; Teti and Gelfand, 1991; Troutman et al, 2012). In the current study, Cronbach’s alpha was 0.68 for the MSES.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores from the ten items were summed to indicate parenting-related self-efficacy (Teti and Gelfand, 1991). The scale has good reliability and validity (Teti and Gelfand, 1991) and has been used in many studies with new mothers during the first postpartum year (Jones and Prinz, 2005; Leerkes and Crockenberg, 2002; Reece and Harkless, 1998; Schneewind and Pfeiffer, 1995; Teti and Gelfand, 1991; Troutman et al, 2012). In the current study, Cronbach’s alpha was 0.68 for the MSES.…”
Section: Methodsmentioning
confidence: 99%
“…Parental self-efficacy, a widely examined psychometric measure of parenthood adjustment, is a mother’s belief in her capacity to effectively manage parenting-related tasks as well as an overall perceived competence in being a parent (Teti and Gelfand, 1991). Parental self-efficacy is important because it plays a role in promoting positive mother-infant relationships (Leerkes and Crockenberg, 2002; Teti and Gelfand, 1991), and in turn positive infant developmental outcomes (Troutman et al, 2012). Although little is understood about brain region(s) responsible for parental self-efficacy, previoius work observed associations between self-efficacy in other domains such as emotion regulation and prefrontal cortex function (Goldin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies 16,18 assessed global self-efficacy beliefs rather than domain general or specific parenting beliefs because they believed it would provide a more comprehensive understanding of parenting confidence when a child has a health condition or disability, whereas domain general or specific measures are tailored to specific issues (e.g., academic performance, obesity, autism, or diabetes management or populations (e.g., adolescents, early childhood, or first time parents). The measure used most often (n=6) to assess PSE was the Parenting Sense of Competence Scale, 9,12,13,17,19,20 a domain-general parenting scale that asks parents to rate perceived sense of competence in the parenting role. Some researchers consider this scale to be consistent with self-efficacy theory because the revised version, has an Efficacy subscale where the authors noted links to self-efficacy theory, although this was not explicit by the authors of the instrument.…”
Section: Literature Review Of Conceptsmentioning
confidence: 99%
“…Some researchers consider this scale to be consistent with self-efficacy theory because the revised version, has an Efficacy subscale where the authors noted links to self-efficacy theory, although this was not explicit by the authors of the instrument. 7 The second most commonly used scale (n=4) was the Maternal Efficacy Questionnaire (MEQ), 12,2123 a domain-specific scale that was created to measure how good a parent feels about their ability to perform tasks associated with caring for their infant. A total of 12 different scales 10,11,14,2429 were used to measure PSE, all of which were created using self-efficacy theory, except for the Parental Self-Agency Scale (for a complete review of scales see 7 ).…”
Section: Literature Review Of Conceptsmentioning
confidence: 99%
“…Temperament is related to personality, although personality also includes cognitive aspects such as beliefs and values (Evans & Rothbart, ). Past work has shown that child (Coleman & Karraker, ; Egberts, Prinzie, Deković, de Haan, & van den Akker, ; Troutman, Moran, Arndt, Johnson, & Chmielewski, ) and parent (Bornstein, Hahn, & Haynes, ; de Haan, Prinzie, & Deković, ) traits are independently associated with parenting self‐perceptions, which, in turn, are associated with parenting behaviors (de Haan et al, ; Egberts et al, ). However, little is known about whether parent and child traits combine to relate to parenting self‐perceptions.…”
Section: Introductionmentioning
confidence: 99%